Genome sequence of the biocontrol strain Pseudomonas fluorescens F113 - Miguel, M.; Barret, M.; Morrisey, J.; Germaine, K.; Francisco, F.; Barahona, E.; Navazo, A.; María, M.; Moynihan, J.; Giddens, S.; Coppoolse, E.; Muriel, C.; et al. (2012)
Pseudomonas fluorescens F113 is a plant growth-promoting rhizobacterium (PGPR) that has biocontrol activity against fungal plant pathogens and is a model for rhizosphere colonization. Here, we present its complete genome sequence, which shows that besides a core genome very similar to those of other strains sequenced within this species, F113 possesses a wide array of genes encoding specialized functions for thriving in the rhizosphere and interacting with eukaryotic organisms. © 2012, American Society for Microbiology.